2013
DOI: 10.1007/s10811-013-0067-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on phosphate utilization of two bloom-forming Microcystis spp. (cyanobacteria) isolated from Lake Taihu (China)

Abstract: Microcystis is a common freshwater bloomdominating cyanobacterial genus. However, the crucial factors that affect the seasonal succession and extent of dominance of different species remain largely unknown. This study investigated inorganic phosphorus (P) uptake, growth, and P utilization of two dominant Microcystis species from Lake Taihu (China) at different P concentrations and temperatures. Compared with Microcystis wesenbergii, Microcystis flosaquae had higher maximum uptake rate and luxury storage coeffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
1
7
1
Order By: Relevance
“…However, our results showed that both M. wesenbergii and M. aeruginosa negatively related to temperature but M. ichthyoblabe positively related to temperature. Yue et al (2014) reported that M. wesenbergii dominated under P-limited condition but we found that M. wesenbergii negatively related to TDP concentration. Some other factors such as iron (Xing et al 2007) and wind shearing (Otten and Paerl 2011) are also important factor for determining the dominant Microcystis morphospecies.…”
Section: Cause Of the Vertical Differencecontrasting
confidence: 65%
“…However, our results showed that both M. wesenbergii and M. aeruginosa negatively related to temperature but M. ichthyoblabe positively related to temperature. Yue et al (2014) reported that M. wesenbergii dominated under P-limited condition but we found that M. wesenbergii negatively related to TDP concentration. Some other factors such as iron (Xing et al 2007) and wind shearing (Otten and Paerl 2011) are also important factor for determining the dominant Microcystis morphospecies.…”
Section: Cause Of the Vertical Differencecontrasting
confidence: 65%
“…Although cyanobacteria already dominated the community under the premise of 31 °C at the end of the experiment, the increase of temperature (+3 °C) further compressed the living space of other algae and led to the absolute dominance of Microcystis . Therefore, our experimental results confirm that the response of experimental subjects to increasing temperature is still significant under the premise of higher ambient temperature and caused the increase of cyanobacterial toxin concentration in water, which were proven by Yue et al and Li et al earlier. Moreover, we found, in agreement with Retnamma et al, that nutrient enrichments also can promote the individual cell volume of Microcystis (Figures – and Table S3).…”
Section: Resultssupporting
confidence: 86%
“…As noted above, P is essential for various cellular functions, including cell structure, energy production, and genetic information storage and transfer (Blank et al 2012, Wagner 2023. Certain microalgae espesially cyanobacteria are known to employ a competitive adaptation strategy, storing P during periods of high availability to support growth during periods of lower P concentration (Carey et al 2012, Yue et al 2013, Jentzsch et al 2023. In the realm of cyanobacterial research, Synechocystis sp.…”
Section: Phosphate Uptake In Microalgaementioning
confidence: 99%